2003
DOI: 10.1063/1.1618937
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and domain pattern of L1 ordered FePt films

Abstract: Magnetic force microscope (MFM) was used to characterize the L10 ordered FePt(001) films sputter deposited directly on MgO(001) substrates at an elevated temperature. With the change of nominal thickness (tN), the morphology varied from isolated particles to continuous films. The coercivity showed a marked change at the percolation boundary of tN≅45 nm, where the film morphology changed from a discontinuous to a continuous state. Below tN=45 nm, the coercivity did not change apparently, though the number of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 9 publications
2
32
0
3
Order By: Relevance
“…This is in good agreement with the reported results for the particles to be in a single domain state. 25,[27][28][29][30][31] This is also in good agreement with the theory of demagnetizing field for smaller particles. The charges developed on the surface will act as a source of demagnetizing field.…”
Section: Magnetic Studiessupporting
confidence: 76%
See 1 more Smart Citation
“…This is in good agreement with the reported results for the particles to be in a single domain state. 25,[27][28][29][30][31] This is also in good agreement with the theory of demagnetizing field for smaller particles. The charges developed on the surface will act as a source of demagnetizing field.…”
Section: Magnetic Studiessupporting
confidence: 76%
“…et al reported 380 nm for spherical particles. 24,25 Xavier et al have reported that the critical size equals to 35-40 nm for spherical particles. 26 Recently, Mahmoud et al reported that the critical size for a single domain particle is 16 nm with M s = 30 emu/gm at H c =280 Oe, and also he reported the maximum M s of 41.82 emu/g for the crystallite size of 30 nm annealed at 1000 o C. 27 Jing et al presented that the particle of size 41.6 nm, gives M s of 45 emu/g at H c =86.3 Oe and reported as a single domain particles.…”
Section: Magnetic Studiesmentioning
confidence: 99%
“…In the low-rate sample, each island is magnetically isolated from all other islands, and the global magnetic properties of the film correspond to the sum of all individual islands. We can estimate the critical size, d C , for single domain behavior using 24 where K u , A, and N are the uniaxial anisotropy, the exchange stiffness constant, and the demagnetization factor, respectively. Using (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The transition from a double domain to a single domain state is not expected to be clear cut, given the fluctuation of the shape and size of the dots. It is interesting to note that the critical single domain size of our in-plane magnetized L1 0 -FePt dots is about half the previously reported values (about 180-340 nm) [24,25] for out-of-plane magnetized dots. The difference is worthy of further investigation.…”
Section: Resultsmentioning
confidence: 70%